Surgical Management of Retraction Pockets: Does Mastoidectomy have a Role? - Dispenza, Francesco; Mistretta, Antonina; Gullo, Federico; Riggio, Francesco; Martines, Francesco (International Archives of Otorhinolaryngology, 2020)
Introduction Retraction pocket is a condition in which the eardrum lies deeper within the middle ear. Its management has no consensus in literature.Objective To assess the role of mastoidectomy in the management of retraction pockets added to a tympanoplasty.Methods Prospective study of patients with retraction pocket and referred to surgery. The patients were randomly assigned to two groups: one managed with tympanoplasty and mastoidectomy and the other group with tympanoplasty only. The minimum follow-up considered was 12 months. The outcomes were: integrity of eardrum, recurrence, and hearing status.Results This study included 43 patients. In 24 cases retraction occurred in the posterior half of the eardrum, and in 19 patients there was clinical evidence of ossicular interruption. The two groups of treatment were composed by: 21 patients that underwent tympanoplasty with mastoidectomy and 22 patients had only tympanoplasty. One case of the first group had a recurrence. In 32 cases patients follow up was longer than 48 months. The average air-bone gap changed from 22.1 dB to 5 dB. The percentage of air-bone gap improvement was assessed at 60% in those patients treated with mastoidectomy, and 64.3% in those without it (p > 0.5).Conclusion Tympanoplasty and ossiculoplasty should be considered to treat atelectatic middle ear and ossicular chain interruption. Mastoidectomy as a way to increase air volume in the ear seems to be a paradox; it does not add favorable prognostic factor to management of retraction pockets.
Keywords: tympanic membrane; mastoidectomy; tympanoplasty; middle ear; ossiculoplasty; otitis media